Analysing historical events and current management strategies of wildfires in Norway - Warda Rafaqat; Pedro Sanchez; Dag Botnen; Nieves Fernandez-Anez (Scientific Reports)
Abstract The behaviour of wildfires and their occurrence are changing worldwide. This change is especially notable in areas where these events were not common and are now gaining strength, such as in Northern Europe. Norway has suffered unexpected periods of dryness and high temperatures, causing a considerable change in the probability of wildfire occurrence. A clear example of this trend was 2018 when unusual weather conditions caused numerous fires to spread nationwide. This changing trend highlights the need to understand and analyse the current situation to mitigate future impacts and losses. This paper examines recent wildfires in Norway by analysing the events that have happened from 2016 to 2023, the period when data is available. While acknowledging that this period may not be extensive enough to predict future patterns, this analysis provides valuable insights into recent trends and occurrences. During this timeframe, Norway experienced an annual average of 1217 wildfires, burning 2019 hectares per year. Wildfires peak in April and May. Southern Norway, particularly the Southeast, experiences more wildfires due to drier conditions and denser populations, while Northern regions have fewer fires. This study also evaluated climatic conditions, highlighting a strong correlation between the Palmer Drought Severity Index (PDSI) anomalies and the severe drying conditions in 2018, along with other climatic factors such as land surface temperature, precipitation, and wind. Additionally, the normative and operational situation is detailed to show the framework around these events. It provides reflections and recommendations to avoid future disasters, emphasizing the need for improved fire safety measures and proactive fire management.